She said she was in the family way Pregnancy and infancy in modern Ireland - Farrell, Elaine (IHR Conference Series, 2012)
She said she was in the family way examines the subject of pregnancy and infancy in Ireland from the seventeenth to the twentieth century. It draws on exciting and innovative research by early-career and established academics, and consider topics that have been largely ignored by historians in Ireland. The book will make an important contribution to Irish women.